Adding value to leachate from grape pomace composting through its use as a culture medium and component of biofertilizer - Russi, Alessandra (Electronic Journal "Fórum Ambiental da Alta Paulista", 2024)
Industrial activities produce substantial amounts of waste and by-products, posing significant environmental risks. Composting emerges as a vital strategy for organic waste decomposition and enhancement. However, composting generates leachate, which can pollute soil and water. Thus, our study aimed to assess the potential of grape pomace composting leachate as a component of a culture medium for Bacillus subtilis F62, a plant growth-promoting bacterium, and as a fertilizer for strawberry plants. Initially, we evaluated the physicochemical properties of the leachate and its impact on bacterial growth at various dilutions. Subsequently, we tested the leachate alone and in combination with the bacterium on micropropagated strawberry plants. Results revealed that despite low carbon and nitrogen concentrations, the leachate facilitated bacterial growth similar to LB medium at 10% and 25% dilutions. Furthermore, both leachate application methods, alone and combined with the bacterium, yielded vigorous strawberry plants, particularly with the biofertilizer containing B. subtilis F62. In conclusion, leachate from grape pomace composting shows promise for bacterial growth and fertilizer development to enhance strawberry plant growth and development.